PENINGKATAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV DI SDN 02 MANISREJO MADIUN MELALUI MODEL PEMBELAJARAN TGT BERBASIS FTB - Hanifah, Wafa Dani; Pratiwi, Cerianing Putri; Sundari, Etik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study is intended to describe the improvement of learning outcomes Indonesian grade IV elementary school students through the Team Games Tournament (TGT) model based on Fun Thinkers Book (FTB) media. This type of research is a Classroom Action Research (PTK) and was conducted at SDN 02 Manisrejo, Madiun. The results of this study show that the FTB media-based TGT learning model is able to significantly improve student learning outcomes Indonesian. This is evidenced by improving student learning outcomes starting from pre-cycle activities, cycle I, and cycle II. Where in the pre-cycle students who completed getting the value of learning outcomes Indonesian above KKM were 9 people with a percentage of 34.6%. In cycle I, students who get learning outcomes above KKM (complete) have increased to 16 people with a percentage of 61.5%. In the second cycle of learning outcomes Indonesian students experienced a significant increase, there were 21 students who completed getting learning outcomes scores above KKM with a percentage of 80.8%. It can be concluded that the FTB media-based TGT learning model can improve learning outcomes Indonesian grade IV students at SDN 02 Manisrejo.